2010
DOI: 10.1177/0956797610381506
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Effect of Education on Health

Abstract: Higher education (or more years of formal schooling) is widely associated with better health, but the underlying causes of this association are unclear. In this study, we tested our schooling-decision-making model, which posits that formal education fosters intellectual ability, which in turn provides individuals with enduring competencies to support better health-related behaviors. Using data from a field study on formal education in 181 adults in rural Ghana, we examined health-protective behaviors related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 25 publications
4
59
0
3
Order By: Relevance
“…This is in line with reports that education results in the more educated less likely to be infected, a negative linear relationship between years of education and HIV [16], [17]. It is noteworthy that although the proportion of illiteracy was low in the present study, the level of attainment and years of study was also low.…”
Section: Discussionsupporting
confidence: 93%
“…This is in line with reports that education results in the more educated less likely to be infected, a negative linear relationship between years of education and HIV [16], [17]. It is noteworthy that although the proportion of illiteracy was low in the present study, the level of attainment and years of study was also low.…”
Section: Discussionsupporting
confidence: 93%
“…But in this case, since all Study-2 participants reported starting and stopping their schooling because of the vicissitudes of subsistence-level farming, finances, access, or gender preferences instead of pre-school cognitive endowments, there is no evidence that variation in attendance and duration was confounded by a cognitiveselection effect or an unmeasured cognitive factor. And these findings are similar to those reported by Peters et al (2010) in a similar study. In addition, Richards, Power, and Sacker (2009) conclude from a series of analyses of British adults that education is likely a causal influence on later-life cognition even after conditioning on social class of origin, childhood intelligence, and subsequent occupational attainment.…”
Section: Discussionsupporting
confidence: 94%
“…If CEFs are profoundly shaped and enhanced by education, these skills may be a plausible mediator of the widely reported associations between education and individuals' health, fertility, and longevity. It also opens a distinctly cognitive perspective on education's observed association with demographic processes and health outcomes at both the individual and population levels (e.g., Baker et al, 2011;Dieckmann et al, in press;Lutz & Samir, 2011;Peters et al, 2010;Rindermann & Gerhard, 2009).…”
Section: Implications Of the Schooling-cognitive Enhancement Hypothesismentioning
confidence: 98%
“…Education teaches people to think for themselves, giving them greater power to make decisions concerning their lifestyle and health (Peters, Baker, Dieckmann, Leon, & Collins, 2010). It is also possible that more years of education is associated with a greater understanding of HIV, and the need to protect oneself actively against it.…”
Section: Years Of Schoolingmentioning
confidence: 99%